Comprehensive Assessment of a Software Development Project for Engineering Instruction - Hall, Richard H; Philpot, Timothy A.; Hubing, Nancy (The Journal of Technology, Learning and Assessment, 2006)
This paper reviews a series of formative assessment studies that were conducted to inform and evaluate a large-scale instructional software development project at the University of Missouri –Rolla (UMR). The three-year project, entitled “Taking the Next Step in Engineering Education: Integrating Educational Software and Active Learning,” was funded by the U.S. Department of Education Fund for the Improvement of Post Secondary Education (FIPSE). The assessment was carried out under the auspices of UMR’s Laboratory for Information Technology Evaluation (LITE) and guided by the LITE model for evaluation of learning technologies. The fundamental premise of the model is that evaluation should consist of the triangulation of multiple research methodologies and measurement tools. Five representative evaluation studies, consisting of eight experiments, are presented here. The studies range from basic experimentation and usability testing to applied research conducted within the classroom as well as a multi-national cross-cultural applied dissemination survey conducted during the last semester of the project. This paper demonstrates that the LITE model can be an effective tool for guiding a comprehensive evaluation program. In addition, the research findings provide evidence that the instructional multimedia developed in this project can have a substantial positive impact in enhancing fundamental engineering classes.